Integrating Moral Education in Islamic Boarding Schools Through the Washoya Book: A Qualitative Study - Sutrisno Sutrisno; Saiful Ahyar; Suhardi Suhardi; Aswan Aswan; Ibnu Alwi Jarkasih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Moral education holds a central role in shaping students' character, particularly within Islamic boarding schools (pesantren). This study explores the integration of moral values through the Washoya Book, a classical Islamic text aimed at guiding students toward ethical behavior in accordance with Islamic teachings. Employing a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews with teachers and students, and document analysis. The study was conducted at a traditional Islamic boarding school in Indonesia. The moral education design was structured around ten selected chapters of the Washoya Book, delivered using traditional Islamic teaching methods—bandongan (lecture-based reading), sorogan (individual reading and explanation), and discussion. The implementation involved structured learning sessions divided into preliminary, core, and closing activities. The findings indicate significant improvements in students’ moral conduct across three domains: (1) moral behavior toward Allah SWT, (2) interpersonal ethics involving teachers and peers, and (3) environmental awareness and responsibility. Learning based on the Washoya Book contributes to the development of students’ moral character, enhancing their devotion, discipline, and respect for others and the environment. The study highlights the relevance of classical Islamic texts in contemporary moral education and suggests the importance of methodical integration within pesantren curricula.